Sense of belonging in hybrid work settings - Urrila, Laura; Siiriainen, Aija; Makela, Liisa; Kangas, Hilpi (Elsevier, 2025)
Despite a wealth of research on flexible work, the understanding of the social and relational implications of hybrid work-a type of flexible work that combines remote and onsite work-is limited. This qualitative study investigates how individuals experience belonging in the hybrid working context. We present findings from 32 interviews conducted at two time-points between 2020 and 2022 with 16 expert employees. Our analysis reveals particular aspects of hybrid work that are related to working remotely (Control over work and personal time; Remote working skills; Virtual communication practices) and working onsite (Human connection; Information exchange; Relevance of onsite work). Based on our research, we theorize how the physical asynchrony attached to working remotely (i.e., alone, usually at home) and the physical synchrony attached to working onsite (i.e., alongside others) may contribute to employees' sense of belonging in hybrid work. We also debate potential early signs of work loneliness, and what might constitute satisfactory work relationships in hybrid work. We encourage future research on psychological needs satisfaction in hybrid work settings and recommend that organizations deploy hybrid working models that support connection.